REPRODUCTIVE CYCLE AND WEIGHT GONADS BANGGAI CARDINAL (Pterapogon Kauderni, KOUMANS 1933) AT DIFFERENT LEVELS OF SALINITY - Atiek Pietoyo (Faculty of Science and Technology University Ibrahimy, 2016)
The purpose of this study to determine the reproductive cycle and gonad weight Banggai Cardinal in salinity treatment. Water quality measurements carried out on a daily basis to maintain water quality. Measurement of water quality, suitability for maintenance Banggai Cardinal. The reproductive cycle is not significantly different at the various treatments. 27 ppt salinity treatment is the treatment that has received positive responses to the gonad weight Banggai Cardinal (0.0018 Â± 0.0498%).